1998
DOI: 10.1177/154193129804200106
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Communication and Situation Awareness in Air Combat

Abstract: In an exploratory study, we examined whether communication could distinguish between high-or low-situation awareness (SA) F-15 lead pilots. With aid from an assigned wingman and an air weapons controller, the lead pilots flew 36 simulated combat engagements. Two measures of SA were utilized. First, ratings of SA were obtained from the operational squadrons. Second, subject matter experts based SA ratings of 40 lead pilots on (a) 28 critical behaviors identified in a task analysis, and (b) behaviors such as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
1
5
1
Order By: Relevance
“…The sharing of necessary information was shown to have a high degree of association with SAGAT scores. This is in line with a previous study by Schreiber et al (1998), who found that high-SA pilots provide more information because they tend to be more aware of the relevant information. Sharing information regarding own and enemy is necessary to build a big picture of the overall team situation.…”
Section: Sa and Teamwork Behaviorsupporting
confidence: 93%
See 2 more Smart Citations
“…The sharing of necessary information was shown to have a high degree of association with SAGAT scores. This is in line with a previous study by Schreiber et al (1998), who found that high-SA pilots provide more information because they tend to be more aware of the relevant information. Sharing information regarding own and enemy is necessary to build a big picture of the overall team situation.…”
Section: Sa and Teamwork Behaviorsupporting
confidence: 93%
“…Similarly, Bowers, Jentsch, Salas, and Braun (1998) analyzed communication patterns of high-and lowperforming cockpit teams and revealed that high-performing teams used more closedloop communication (i.e., following commands and actions with acknowledgment and response). In contrast, Schreiber, Bell, and Raspotnik (1998) found that pilots with higher SA acknowledged less. MacMillan, Entin, and Serfaty (2004) showed that efficiency of communication, measured in terms of anticipation ratio (i.e., ratio of the number of communications transferring information to the number of communications requesting information), correlates to team outcome measures.…”
Section: Teamwork Behavior and Communicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, cognitive constructs such as memory, mental pictures, attention, and schemata (Endsley, 1995b;Wilson, 1995), are outside the purview of the ELM. Furthermore, the approach is not equipped to capture the relationships between SA and communication (Schreiber, Bell and Raspotnik, 1998), or the emotional and phenomenological aspects of SA (Gerson, 1997).…”
Section: Ss Skill Scorementioning
confidence: 99%
“…When the numbers of thought units in each category were transformed into a percentage of the total units communicated (see Table 4-4), the percentage of information request and response were found to significantly correlate to navigation errors, r = .93, p < .01 and r = .95, p < .01, respectively. Previous study by Hollenbeck et al (1995) Contrary to the findings by Hollenbeck et al (1995), Schreiber and colleagues (Schreiber et al, 1998;Schreiber et al, 1996) reported that high SA pilots requested more information. The latter finding is similar to the trend found in the enemy engagement task,…”
Section: Differences Across Teams Team Performancementioning
confidence: 69%